The Ectopic Overexpression of the Cotton Ve1 and Ve2-Homolog Sequences Leads to Resistance Response to Verticillium Wilt in Arabidopsis - Chen, Jieyin; Li, Nanyang; Ma, Xuefeng; Gupta, Vijai K.; Zhang, Dandan; Li, Tinggang; Dai, Xiaofeng (Frontiers in Plant Science, 2017)
Verticillium wilt, caused by the Verticillium dahliae phytopathogen, is a devastating disease affecting many economically important crops. A receptor-like protein (RLP) gene, Ve1, has been reported to confer resistance to V. dahliae in tomato plants, but few genes have been found to be involved in cotton Verticillium wilt resistance. Here, we cloned two RLP gene homologs, Gossypium barbadense resistance gene to Verticillium dahliae 1 (GbaVd1) and GbaVd2, from the Verticillium wilt-resistant cultivar G. barbadense cv. Hai7124. GbaVd1 and GbaVd2 display sequence divergence, but both encode typical RLPs. Virus-induced gene silencing of GbaVd1 or GbaVd2 compromised the resistance of cotton to V. dahliae, and both genes conferred Verticillium wilt resistance after interfamily transfer into Arabidopsis. Microarray analysis revealed that GbaVd1 and GbaVd2 participate in Verticillium wilt resistance in Arabidopsis through activation of defense responses, including the endocytosis process, signaling factors, transcription factors and reinforcement of the cell wall, as demonstrated by lignification in Arabidopsis transgenic plants. In addition, microarray analysis showed that GbaVd1 and GbaVd2 differentially mediate resistance signaling and activation of defense responses after overexpression in Arabidopsis. Thus, GbaVd1 and GbaVd2 encode RLPs and act as disease resistance genes that mediate the defense response against V. dahliae in cotton.